Carbon and Nitrogen in the Terrestrial Environment - Nieder (Springer, 2012)
Carbon and Nitrogen in the Terrestrial Environment is a comprehensive, interdisciplinary description of C and N fluxes between the atmosphere and the terrestrial biosphere; issues related to C and N management in different ecosystems and their implications for the environment and global climate change; and the approaches to mitigate emission of greenhouse gases.